Azole Resistance and ERG11 Mutation in Clinical Isolates of Candida tropicalis - Adriele Celine Siqueira; Gisele Aparecida Bernardi; Lavinia Nery Villa Stangler Arend; Gabrielle Tomé Cordeiro; Daiane Rosolen; Fernanda Costa Brandão Berti; Amanda Maria Martins Ferreira; Thaís Muniz Vasconcelos; Bianca Cruz Neves; Luiza Souza Rodrigues; Libera Maria Dalla-Costa (Journal of Fungi)
We investigated the molecular mechanisms underlying azole resistance in seven Candida tropicalis isolates that caused candidemia and candiduria in Paraná, Brazil (2016–2022). Biofilm production, antifungal susceptibility testing, multilocus sequence typing, amplification and sequencing of ERG11, and quantification of ERG11, MDR1, and CDR1 expression levels were performed. Notably, five isolates (71.4%) were from urine samples and two (28.6%) were from blood samples. All strains were biofilm producers, with levels ranging from moderate to strong. The minimum inhibitory concentration (MIC) values ranged from 8–>64 mg/L for fluconazole and 0.25–1 mg/L for voriconazole. All isolates had mutations in ERG11; Y132F and Y257N were predominant (71.4%), followed by Y132F and S154F (14.3%) and Y257H (14.3%). No differences in ERG11 expression were found between the susceptible and resistant groups, but MDR1 and CDR1 were more highly expressed in the susceptible isolates. All the isolates contained previously unassigned diploid sequence types. The emergence of C. tropicalis azole resistance has been previously described in Brazil; however, the presence of resistant isolates in urine highlights the need for surveillance resistant strains in both urinary and invasive contexts. In our study mutations in ERG11 were the main resistance mechanism identified in C. tropicalis.